Vous êtes sur la page 1sur 18

# Section 2.

3
θ
C02S03.001: θ · → 0 · 1 = 0 as θ → 0.
sin θ
sin θ sin θ
C02S03.002: · → 1 · 1 = 1 as θ → 0.
θ θ
C02S03.003: Multiply numerator and denominator by 1 + cos θ (the conjugate of the numerator) to obtain

## 1 − cos2 θ sin θ sin θ 1 1 1

lim = lim · · =1·1· = .
θ→0 θ2 (1 + cos θ) θ→0 θ θ 1 + cos θ 2 2

## tan θ sin θ sin θ 1 1

C02S03.004: = = · → 1 · = 1 as θ → 0.
θ θ cos θ θ cos θ 1
C02S03.005: Divide each term in numerator and denominator by t. Then it’s clear that the denominator
is approaching zero whereas the numerator is not, so the limit does not exist. Because the numerator is
positive and the denominator is approaching zero through negative values, the answer −∞ is also correct.

## sin 2ω 2 sin ω cos ω sin ω

= = · 2 cos ω → 1 · 2 · 1 = 2.
ω ω ω

sin 5x 5 sin z
C02S03.007: Let z = 5x. Then z → 0 as x → 0, and = → 5 · 1 = 5.
x z
sin 2z 2 sin z cos z 2 cos z sin z 1
C02S03.008: = = · → 2 · · 1 = 2 as z → 0.
z cos 3z z cos 3z cos 3z z 1

C02S03.009: This limit does not exist because x is not deﬁned for x near 0 if x < 0. But
 
sin x √  sin x
lim √ = lim x · = 0 · 1 = 0.
x→0+ x x→0+ x

C02S03.010: Using the identity sin2 x = 12 (1 − cos 2x) (inside the front cover), we obtain

## 1 − cos 2x 2(1 − cos 2x) 2 sin2 x sin x

lim = lim = lim = lim (2 sin x) = 2 · 0 · 1 = 0.
x→0 x x→0 2x x→0 x x→0 x
Alternatively, you could multiply numerator and denominator by 1+cos 2x (the conjugate of the numerator).

## C02S03.011: Let x = 3z. Then x → 0 is equivalent to z → 0, and therefore

1 x 1 1 sin z 1 1
lim sin = lim sin z = lim · = ·1= .
x→0 x 3 z→0 3z z→0 3 z 3 3

## (sin 3θ)2 (sin x)2 sin x sin x 1 1

lim = lim 1 2
  = lim 9 · · ·   = 9 · 1 · 1 · = 9.
θ→0 θ2 cos θ x→0
9x cos 13 x x→0 x x cos 13 x 1

C02S03.013: Multiply numerator and denominator by 1 + cos x (the conjugate of the numerator) to obtain

1
(1 − cos x)(1 + cos x) 1 − cos2 x sin2 x sin x 0
lim = lim = lim = lim = = 0.
x→0 (sin x)(1 + cos x) x→0 (sin x)(1 + cos x) x→0 (sin x)(1 + cos x) x→0 1 + cos x 1+1

## C02S03.014: By Problem 4, (tan x)/x → 1 as x → 0. This observation implies that

tan kx kx
lim =1 and lim =1
x→0 kx x→0 tan kx
for any nonzero constant k. Hence

tan 3x 3 tan 3x 5x 3 3
lim = lim · · = ·1·1= .
x→0 tan 5x x→0 5 3x tan 5x 5 5

1 1
C02S03.015: Recall that sec x = and csc x = . Hence
cos x sin x
1 x 1
lim x sec x csc x = lim · = · 1 = 1.
x→0 x→0 cos x sin x 1
We also used the fact that

x 1 1
lim = lim = = 1.
x→0 sin x x→0 sin x 1
x

## sin 2θ 2 sin θ cos θ sin θ

C02S03.016: lim = lim = lim (2 cos θ) · = 2 · 1 · 1 = 2.
θ→0 θ θ→0 θ θ→0 θ

C02S03.017: Multiply numerator and denominator by 1 + cos θ (the conjugate of the numerator) to obtain

## (1 − cos θ)(1 + cos θ) sin2 θ sin θ

lim = lim = lim
θ→0 (θ sin θ)(1 + cos θ) θ→0 (θ sin θ)(1 + cos θ) θ→0 θ(1 + cos θ)

sin θ 1 1 1
= lim · =1· = .
θ→0 θ 1 + cos θ 1+1 2

sin2 θ sin θ
C02S03.018: lim = lim · sin θ = 1 · 0 = 0.
θ→0 θ θ→0 θ
tan z sin z 1 1 1
C02S03.019: lim = lim = lim = = .
z→0 sin 2z z→0 (cos z)(2 sin z cos z) z→0 2 cos2 z 2 · 12 2

tan 2x 2 tan 2x 2 2
C02S03.020: lim = lim · = ·1= (with the aid of Problem 4).
x→0 3x x→0 3 2x 3 3
x cos 3x 3x cos 3x 1 1
C02S03.021: lim x cot 3x = lim = lim · = 1· = (see Problem 15, last line).
x→0 sin 3x
x→0 x→0 sin 3x 3 3 3
 
x tan x

x − tan x x x 1−1
C02S03.022: lim = lim   = = 0 (with the aid of Problem 4).
x→0 sin x x→0 sin x 1
x

## C02S03.023: Let x = 12 t. Then x → 0 is equivalent to t → 0, so

2
 
t
sin
2 sin x
lim = lim = 1.
t→0 t x→0 x
2

Therefore

   2
t
    sin
1 t 1 4 t 1  2 
 = 1 · 12 = 1 .
lim 2 sin2
= lim · 2 sin2
= lim · 
 
t→0 t 2 t→0 4 t 2 t→0 4 t 4 4
2

sin x
C02S03.024: Because → 1 as x → 0, it follows that
x

sin kx kx
lim =1 and lim =1
x→0 kx x→0 sin kx

## for any nonzero constant k. Hence

sin 2x 2 sin 2x 5x 2 2
lim = lim · · = ·1·1= .
x→0 sin 5x x→0 5 2x sin 5x 5 5

C02S03.025: Because −1  cos 10x  1 for all x, −x2  x2 cos 10x  x2 for all x. But both −x2 and x2
approach zero as x → 0. Therefore lim x2 cos 10x = 0. The second inequality is illustrated next.
x→0

## -1.5 -1 -0.5 0.5 1 1.5

-1

-2

1
C02S03.026: Because −1  sin x  1 for all x, also −x2  x2 sin  x2 for all x = 0. Because both −x2
x
1
and x2 approach zero as x → 0, it follows from the squeeze law that lim x2 sin = 0. The second inequality
x→0 x
is illustrated next.

3
0.075

0.05

0.025

-0.025

-0.05

-0.075

## C02S03.027: First, −1  cos x  1 for all x. Therefore

1
−x2  x2 cos √  x2
3
x

for all x = 0. Finally, both x2 and −x2 approach zero as x → 0. Therefore, by the squeeze law,

1
lim x2 cos √ = 0.
x→0 3
x

## C02S03.028: Because −1  sin x  1 for all x,

√ √ 1 √
− 3 x  3 x sin  3 x
x
√ √
for all x = 0. Because both − | 3 x | and | 3 x | approach zero as x → 0, it follows from the squeeze law that

3
1
lim x sin = 0.
x→0 x

 √ 
C02S03.029: lim 3− x =3− lim+ x = 3 − 0 = 3.
x→0+ x→0

   3/2
C02S03.030: lim 4 + 3x 3/2
=4+3· lim x = 4 − 3 · 0 = 4.
x→0+ x→0+

C02S03.031: lim x − 1 does not exist because if x < 1, then x − 1 < 0.
x→1−

C02S03.032:
√ √ x → 4 , x < 4, so that
Because 4 − x is deﬁned for all such x. Therefore the limit exists
and lim 4 − x = 4 − 4 = 0.

x→4

C02S03.033:
 Because
√ x → 2+ , x > 2, so that x2 > 4. Hence x2 − 4 is deﬁned for all such x and
lim+ x − 4 = 4 − 4 = 0.
2
x→2

C02S03.034: Because x → 3+ , x > 3, so that 9 − x2 < 0 for all such x. Thus the given limit does not
exist.

4
C02S03.035:  Because x → 5− , x < 5 and x > 0 for x suﬃciently close to 5. Therefore x(5 − x) > 0 for
such x, so that x(5 − x) exists for such x. Therefore
  
 √
lim

x(5 − x) = lim x 5 − lim x = 5 · 0 = 0.
− −
x→5 x→5 x→5

C02S03.036:
√ As x → 2− , x <  −2 for x suﬃciently
2, and x >  √ close to 2. For such x, 4 − x2 > 0, so that
4 − x exists. Therefore lim− 4 − x = 4 − 2 = 0 = 0.
2 2 2
x→2

C02S03.037: As x → 4+ , x > 4, so that both 4x and x − 4 are positive. Hence the radicand is positive
and the square root exists. But the denominator in the radicand is approaching zero through positive values
while the numerator is approaching 16. So the fraction is approaching +∞. Therefore

4x
lim = +∞.
x→4+ x−4
It is also correct to say that this limit does not exist.

C02S03.038: First, 6 − x − x2 = (3 + x)(2 − x), so that as x → −3+ , x > −3, and thus 3 + x > 3 − 3 = 0.
Also x < 2 if x is suﬃciently close to −3, so that 2 − x > 0. Therefore (3 + x)(2 − x) > 0, and so the square
root is deﬁned. Finally,
  √ √
lim 6 − x − x2 = lim (3 + x)(2 − x) = 0·5= 0 = 0.
x→−3+ x→−3+

x−5 x−5
C02S03.039: If x < 5, then x − 5 < 0, so = = −1. Therefore the limit is −1.
|x − 5| −(x − 5)

16 − x2 √
C02S03.040: If −4 < x < 4, then 16 − x2 > 0, so √ = 16 − x2 → 0 as x → −4+ .
16 − x 2

x2 − 6x + 9 |x − 3| x−3
C02S03.041: If x > 3, then x −6x+9 = (x−3) > 0 and x−3 > 0, so
2 2
= = →1
x−3 x−3 x−3
as x → 3+ .
x−2 x−2 1
C02S03.042: = = → −1 as x → 2+ . Indeed, the two-sided limit exists
x2 − 5x + 6 (x − 2)(x − 3) x−3
and is equal to −1.

2−x 2−x
C02S03.043: If x > 2 then x − 2 > 0, so = = −1. Therefore the limit is also −1.
|x − 2| x−2

7−x 7−x
C02S03.044: If x < 7 then x − 7 < 0, so = = 1. So the limit is 1.
|x − 7| −(x − 7)

1 − x2 (1 + x)(1 − x)
C02S03.045: = = 1 + x, so the limit is 2.
1−x 1−x

## C02S03.046: As x → 0− , x < 0, so that x − |x| = x − (−x) = 2x. Therefore

x x 1 1
lim = lim− = lim− = .
x→0− x − |x| x→0 2x x→0 2 2

5

 Recall ﬁrst that z = |z | for every real number z. Because x → 5 , x > 5, so 5 − x < 0.
2 +
C02S03.047:
Therefore (5 − x)2 = |5 − x| = −(5 − x) = x − 5. Therefore

(5 − x)2 x−5
lim = lim+ = lim+ (−1) = −1.
x→5 + 5 − x x→5 5 − x x→5

C02S03.048: Recall that z 2 = |z | for every real number z. Because x → −4− , we know that x < −4.
Hence 4 + x < 4 + (−4) = 0. Therefore

## 4+x 4+x 4+x

lim  = lim = lim = lim (−1) = −1.
x→−4− (4 + x)2 x→−4− |4 + x| x→−4 −(4 + x)
− x→−4−

C02S03.049: The right-hand and left-hand limits both fail to exist at a = 1. The behavior of f near a is
best described by observing that

1 1
lim = +∞ and lim = −∞.
x→1+ x−1 x→1− x−1

C02S03.050: The right-hand and left-hand limits both fail to exist at a = 3. The behavior of f near a is
best described by observing that

2 2
lim = −∞ and lim = +∞.
x→3+ 3−x x→3− 3−x

C02S03.051: The right-hand and left-hand limits both fail to exist at a = −1. The behavior of f near a
is best described by observing that

x−1 x−1
lim = −∞ and lim = +∞.
x→−1+ x+1 x→−1− x+1

C02S03.052: The right-hand and left-hand limits both fail to exist at a = 5. The behavior of f near a is
best described by observing that

2x − 5 2x − 5
lim = −∞ and lim = +∞.
x→5+ 5−x x→5− 5−x

C02S03.053: The right-hand and left-hand limits both fail to exist at a = −2. If x is slightly greater than
−2, then 1 − x2 is close to 1 − 4 = −3, while x + 2 is a positive number close to zero. In this case f (x) is
a large negative number. Similarly, if x is slightly less than −2, then 1 − x2 is close to −3, while x + 2 is a
negative number close to zero. In this case f (x) is a large positive number. The behavior of f near −2 is
best described by observing that

1 − x2 1 − x2
lim = −∞ and lim − = +∞.
x→−2+ x+2 x→−2 x+2

C02S03.054: The right-hand and left-hand limits fail to exist at a = 5. If x is close to 5 but x = 5, then
x − 5 is close to zero, so that (x − 5)2 is a positive number still very close to zero. Its reciprocal is therefore
a very large positive number. That is,

1 1
lim = lim− = +∞. (1)
x→5+ (x − 5)2 x→5 (x − 5)2

6
Unlike the previous problems of this sort, we may in this case also write

1
lim = +∞.
x→5 (x − 5)2

Nevertheless, Eq. (1) implies that neither the left-hand nor the right-hand limit of f (x) exists (is a real
number) at x = 5.

C02S03.055: The left-hand and right-hand limits both fail to exist at x = 1. To simplify f (x), observe
that

|1 − x| |1 − x| 1
f (x) = = = .
(1 − x)2 |1 − x|2 |1 − x|

## Therefore we can describe the behavior of f (x) near a = 1 in this way:

1
lim f (x) = lim = +∞.
x→1 x→1 |1 − x|

C02S03.056: Because x2 + 6x + 9 = (x + 3)2 , the denominator in f (x) is zero when x = −3, and so the
left-hand and right-hand limits fail to exist at a = −3. When x is close to −3 but x = −3, (x + 3)2 is a
positive number very close to zero, while the numerator x + 1 is close to −2. Therefore f (x) is a very large
negative number. That is,

x+1
lim = −∞.
x→−3 x2 + 6x + 9

## C02S03.057: First simplify f (x): If x2 = 4 (that is, if x = ±2), then

x−2 x−2 −1
f (x) = = = .
4−x2 (2 + x)(2 − x) 2+x

So even though f (2) does not exist, there is no real problem with the limit of f (x) as x → 2:

−1 1
lim f (x) = lim =− .
x→2 x→2 2+x 4
But the left-hand and right-hand limits of f (x) fail to exist at x = −2, because

−1 −1
lim f (x) = lim = −∞ and lim f (x) = lim = +∞.
x→−2+ x→−2+ 2+x x→−2− x→−2− 2+x

## C02S03.058: First simplify:

x−1 x−1 1
f (x) = = =
x2 − 3x + 2 (x − 1)(x − 2) x−2

## if x = 1 and x = 2. But even though f (1) is undeﬁned,

1 1
lim f (x) = lim = = −1.
x→1 x→1 x−2 1−2
But the one-sided limits fail to exist at x = 2:

1 1
lim f (x) = lim = +∞ and lim f (x) = lim− = −∞.
x→2+ +
x→2 x−2 x→2− x→2 x−2

7
x2 − 4 x2 − 4
C02S03.059: lim+ = 4 and lim = −4. The two-sided limit does not exist. The graph is
x→2 |x − 2| x→2 |x − 2|

shown next.

1.5 2 2.5 3

-2

-4

x4 − 8x + 16 x4 − 8x + 16
C02S03.060: Because lim = +∞ and lim = +∞, the two-sided limit also
x→2+ |x − 2| x→2− |x − 2|
fails to exist. The graph is shown next.

2000

1500

1000

500

1.5 2 2.5 3

C02S03.061: If x is an even integer then f (x) = 3, if x is an odd integer then f (x) = 1, and lim f (x) = 2
x→a
for all real number values of a. The graph of f is shown next.

-1 1 2 3 4

C02S03.062: If n is any integer then f (x) → n as x → n. Note: lim f (x) = a for all real number values
x→a

8
of a. The graph of f is shown next.

-1 1 2 3 4
-1

C02S03.063: For any integer n, lim f (x) = 10n − 1 and lim f (x) = 10n. Note: lim f (x) exists if and
− x→n + x→n x→a
only if 10a is not an integer. The graph is shown next.

## -0.2 -0.1 0.1 0.2 0.3 0.4

-1

-2

-3

C02S03.064: If n is an odd integer, then f (x) = n − 1, an even integer, for n − 1  x < n and f (x) = n,
an odd integer, for n  x < n + 1. Therefore

x→n− x→n+

## lim f (x) = −1 and lim f (x) = 1.

x→n− x→n+

Finally, lim f (x) exists if and only if a is not an integer. The graph of f is shown next.
x→a

9
1

0.5

-1 1 2 3 4

-0.5

-1

C02S03.065: If n is an integer and n < x < n + 1, then write x = n + t where 0 < t < 1. Then
f (x) = n + t − n − 12 = t − 12 . Moreover, x → n+ is equivalent to t → 0+ . Therefore

    1
lim f (x) = lim t − 12 = lim t − 12 = − .
x→n + x→n + t→0 + 2

## Similar reasoning, with n − 1 < x < n, shows that if n is an integer, then

1
lim f (x) = .
x→n− 2

Finally, if a is a real number other than an integer, then lim f (x) exists. The graph of f is next.
x→a

0.4

0.2

-1 1 2 3 4

-0.2

-0.4

C02S03.066: Given the real number x, there is a [unique] integer n such that 2n  x < 2n + 2. Thus
n  12 x < n + 1, and in this case f (x) = n. So if m = 2n is an even integer, then f (x) → m as x → m+ and
x → a for every real number a strictly between 2n and 2n + 2. But if 2n − 2 < x < 2n, then n − 1 < 12 x < n,
so that f (x) = n − 1; in this case f (x) → n − 1 as x → m− . Therefore:

x→k

## If k is an even integer, then lim f (x) = 12 k and lim f (x) = 12 (k − 2).

x→k+ −x→k

Finally, lim f (x) exists if and only if a is not an even integer. The graph of f is next.
x→a

10
3

-2 2 4 6

-1

-2

C02S03.067: If x is an integer, then f (x) = x − x = 0. If x is not an integer, choose the [unique] integer
n such that n < x < n + 1. Then −(n + 1) < −x < −n, so f (x) = n − (n + 1) = −1. Therefore

x→a x→a

x→n− x→n+

-1 1 2 3 4

-0.5

-1

-1.5

-2

## C02S03.068: If n is a positive integer, then

n−1
lim f (x) = and lim f (x) = 1.
x→n− n x→n+

## For any integer n < 0,

n+1
lim f (x) = and lim+ f (x) = 1.
x→n− n x→n

Also,

## lim f (x) = +∞ and lim f (x) = 0.

x→0− x→0+

11
Note: lim f (x) exists if and only if a is not an integer. The graph of f is next.
x→a

-1 1 2 3 4

C02S03.069: The values of a for which lim g(x) exists are those real numbers not integral multiples of
x→a
1 1
10 . If b is an integral multiple of 10 , then

lim g(x) = b − 1
10 and lim g(x) = b.
x→b− x→b+

0.4

0.3

0.2

0.1

## -0.2 -0.1 0.1 0.2 0.3 0.4

-0.1

-0.2

-0.3

C02S03.070: Let f (x) = sgn(x) and g(x) = −sgn(x). Clearly neither f (x) nor g(x) has a limit as x → 0
(for example, f (x) → 1 as x → 1+ but f (x) → −1 as x → 1− ). But

 1−1
 if x > 0,
f (x) + g(x) = −1 + 1 if x < 0,

0+0 if x = 0,

## so that f (x) + g(x) ≡ 0, and therefore f (x) + g(x) → 0 as x → 0. Also,


−1 if x = 0,
f (x) · g(x) =
0 if x = 0.
Therefore lim f (x) · g(x) = −1.
x→0

C02S03.071: Because −x2  f (x)  x2 for all x and because −x2 → 0 and x2 → 0 as x → 0, it follows
from the squeeze law for limits that lim f (x) = 0 = f (0).
x→0

12
C02S03.072: As x → 0+ , 1/x → +∞, so 1 + 21/x → +∞ as well. Therefore

1
lim = 0.
x→0+ 1 + 21/x

## As x → 0− , 1/x → −∞, so 21/x → 0. Consequently,

1
lim = 1.
x→0− 1 + 21/x

Therefore lim f (x) does not exist. This function approaches its one-sided limits at x = 0 very rapidly. For
x→0
example,

## The graph of f for x near zero is next.

0.8

0.6

0.4

0.2

-1 1 2 3 4

C02S03.073: Given: f (x) = x · [[1/x]]. Let’s ﬁrst study the right-hand limit of f (x) at x = 0. We need
consider only values of x in the interval (0, 1), and if 0 < x < 1 then

1 1
1< , so that n <n+1
x x

1 1
<x .
n+1 n

## Therefore f (x) = x · n, so that

n n
< f (x)  = 1. (1)
n+1 n

## As x → 0+ , n → ∞, so the bounds on f (x) in (1) both approach 1. Therefore

lim f (x) = 1.
x→0+

A similar (but slightly more delicate) argument shows that f (x) → 1 as x → 0− as well. Therefore lim f (x)
x→0
exists and is equal to 1. The graph of f is next.

13
1.6

1.4

1.2

## -1.5 -1 -0.5 0.5 1 1.5

0.8

0.6

0.4

C02S03.074: Here, f (x) is obtained from the function in Problem 73 by multiplication by x. Therefore,
because the function in Problem 73 had limit 1 as x → 0, the product rule for limits implies that f (x) →
0 · 1 = 0 as x → 0. The graph of f near zero is next.

0.4

0.2

-0.2

-0.4

-0.6

Then


|x + 3| < ;
7
|7x + 21| < ;

## Therefore, by deﬁnition, lim (7x − 9) = −30.

x→−3

C02S03.076: Given  > 0, let δ = /17. Suppose that 0 < |x − 5| < δ. Then

14
|17x − 85| < 17δ;

## Therefore, by deﬁnition, lim (17x − 35) = 50.

x→5

C02S03.077: Deﬁnition: We say that the number L is the right-hand limit of the function f at x = a
provided that, for every  > 0, there exists δ > 0 such that, if 0 < |x−a| < δ and x > a, then |f (x)−L| < .

To prove that lim x = 0, suppose that  > 0 is given. Let δ = 2 . Suppose that |x − 0| < δ and
x→0+ √
that x > 0. Then 0 < x < δ = 2 . Hence x < , and therefore

| x − 0| < .

So, by deﬁnition, lim x = 0.
x→0+

C02S03.078: Let  > 0 be given. Let δ =  . Suppose that 0 < |x − 0| < δ. Then 0 < x2 < δ 2 = .
Hence |x2 − 0| < . Therefore, by deﬁnition,

lim x2 = 0.
x→0

C02S03.079: Suppose that  > 0 is given. Let δ be the minimum of the two numbers 1 and /5 and
suppose that 0 < |x − 2| < δ. Then

|x − 2| < 1;

− 1 < x − 2 < 1;

3 < x + 2 < 5;

|x + 2| < 5.

Therefore

|x2 − 4| = |x + 2| · |x − 2| < 5 · δ  5 · = .
5
Hence, by deﬁnition, lim x2 = 4.
x→2

C02S03.080: Given  > 0, choose δ to be the minimum of 1 and /10. Suppose that 0 < |x − 7| < δ. Then

|x − 7| < 1;

− 1 < x − 7 < 1;

## 8 < x + 2 < 10;

|x + 2| < 10.

Therefore

|(x2 − 5x − 4) − 10| = |x + 2| · |x − 7| < 10 · δ  10 · = .
10

15
Thus, by deﬁnition, lim (x2 − 5x − 4) = 10.
x→7

C02S03.081: Given  > 0, let δ be the minimum of 1 and /29. Suppose that 0 < |x − 10| < δ. Then

## 0 < |x − 10| < 1;

− 1 < x − 10 < 1;

− 2 < 2x − 20 < 2;

## |2x + 7| < 29.

Thus

|(2x2 − 13x − 25) − 45| = |2x + 7| · |x − 10| < 29 · δ  29 · = .
29
Therefore, by deﬁnition, lim (2x2 − 13x − 25) = 45.
x→10

C02S03.082: Given  > 0, choose δ to be the minimum of 1 and /19. Suppose that 0 < |x − 2| < δ. Then

0 < |x − 2| < 1;

− 1 < x − 2 < 1;

1 < x < 3;

## |x2 + 2x + 4| < 19.

Consequently,

|x3 − 8| = |x2 + 2x + 4| · |x − 2| < 19 · δ  19 · = .
19
Therefore, by deﬁnition, lim x3 = 8.
x→2

## C02S03.083: In Problem 78 we showed that if a = 0, then

lim x2 = lim x2 = 0 = 02 = a2 ,
x→a x→0

so the result we are to prove here holds when a = 0. Next case: Suppose that a > 0. Let  > 0 be given.
Choose δ to be the minimum of the numbers 1 and /(2a+1). Note that δ > 0. Suppose that 0 < |x−a| < δ.
Then

|x − a| < 1;

− 1 < x − a < 1;

16
2a − 1 < x + a < 2a + 1;

|x + a| < 2a + 1.

Thus

|x2 − a2 | = |x + a| · |x − a| < (2a + 1) · = .
2a + 1

## Therefore, by deﬁnition, lim x2 = a2 if a > 0.

x→a
Final case: a < 0. Given  > 0, let
 

δ = min 1, .
|2a − 1|

## Note that δ > 0. Suppose that 0 < |x − a| < δ. Then

|x − a| < 1;

− 1 < x − a < 1;

2a − 1 < x + a < 2a + 1;

|x + a| < |2a − 1|

## (because |2a − 1| > |2a + 1| if a < 0). It follows that


|x2 − a2 | = |x + a| · |x − a| < |2a − 1| · = .
|2a − 1|

## Therefore, by deﬁnition, lim x2 = a2 if a < 0.

x→a

C02S03.084: Suppose that  > 0 is given. Case (1): a = 0. Let δ = 3
 and proceed much as in the
solution of Problem 78. Case (2): a > 0. Let
 
a 4
δ = min , .
2 19a2

## Note that δ > 0. Suppose that 0 < |x − a| < δ. Then:

a
|x − a| < ;
2
a a
− < x−a < ;
2 2
a 3a
< x < ;
2 2
a2 9a2
< x2 < (because x > 0);
4 4
a2 3a2
< ax < ;
2 2
3a2 15a2
< x2 + ax < ;
4 4

17
7a2 19a2
< x2 + ax + a2 < ;
4 4
19a2
|x2 + ax + a2 | < .
4
Therefore

19a2 4
|x3 − a2 | = |x2 + ax + a2 | · |x − a| < · = .
4 19a2
Thus, by deﬁnition, lim x2 = a2 if a > 0. Case (3), in which a < 0, is similar.
x→a

18